Pembungaan Jarak Pagar (Jatropha curcas L.) beberapa Ekotipe Nusa Tenggara Barat - Bambang Budi Santoso (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2011)
The fl owering biology of physic nut (Jatropha curcas L.) has been observed in dry land (sandy entisol soil type) of AmorAmor, North Lombok, West Nusa Tenggara. Exploration was conducted in several areas where high population of physic nut grown as fence plant was found. Quantitative, descriptive, and observation data were collected for each accession during two-year growth period. Randomized block design was used in this research with three replications from November 2006 until November 2008. Treatments consisted of fi ve ecotypes, i.e. West Lombok, Central Lombok, East Lombok, Sumbawa, and Bima. The results showed that fl owering of physic nut West Nusa Tenggara ecotypes was produced continuously during a year, while the peak number of fl ower was only twice e.g. at the early (November-February) and at the end (April–May) of rainy season. Duration of the fl owering process took around 3 days for female fl ower, around 2 days for male fl ower, and 7-10 days for total fl ower per infl orescence. Higher genetic potential for female fl ower formation was found on West Lombok, Sumbawa, and Bima ecotype. This result should be useful information for breeding programme of physic nut. However, since physic nut is a perennial plant, further study is needed especially on the technology to control fl owering. Keywords: dry season, fl owering, fruiting, rainy season,